Dynamic splitting tensile performance of new and old concrete after high temperature treatment - Hai Cao (Archives of Civil Engineering, 2021)
In order to study the dynamic splitting tensile properties of new and old concrete after high temperature treatment, the effects of different impact velocities and temperatures on failure modes, dynamic splitting strength and energy absorption of new and old concrete were analyzed by impact dynamic splitting tensile test use of variable cross-section Φ 74 mm split Hopkinson pressure bar apparatus. The results show that: Impact velocity and temperature not only affect the dynamic splitting strength of new and old concrete bonding specimens, but also affect the failure modes and degree of breakage. The dynamic splitting strength of new and old concrete increases with the increase of impact velocity, but the increase rate decreased with the increase of temperature. The dynamic splitting strength first increases slowly and then decreases dramatically with the increase of temperature. In the dynamic splitting test of new and old concrete, the energy absorption increases with the increase of impact velocity and decreases with the increase of temperature.